Thursday

April 24, 2014

April 24, 2014

Posted by **Brianna** on Monday, September 26, 2011 at 9:44am.

- College Algebra -
**Anonymous**, Monday, September 26, 2011 at 9:55amg ( x ) = - 2 * x ^ 2 + b * x + c

For:

x = 0

y= 5

Then:

g( x ) = - 2 * 0 ^ 2 + 0 * x + c = 5

g( x ) = c = 5

c = 5

For:

x= 1

y = 0

g ( x ) = - 2 * 1 ^ 2 + b * 1 + c = 0

g ( x ) = - 2 + b + c = 0

g ( x ) = - 2 + b + 5 = 0

g ( x ) = b + 3 = 0

b = -3

**Related Questions**

college Algebra - Let g(x) = -2x2 + bx + c be a quadratic function, defined ...

Algebra - If the sides perpendicular to the wall have length x feet, which of ...

algebra - Put the equation in the form ax2 + bx + c = 0. Enter exponents using ...

Algebra - Determine the number of real-number solutions to the equation -2x2 - x...

****college algebra**** - Let g(x) be a rational function with a numerator of ...

college algebra - Let g(x) be a rational function with a numerator of 6x2 + 12x...

$$college algebra$$ - Consider g(x) = -2x2 + 36x - 142 for x > 9. Find g-1(12...

algebra - Can someone help me solve this: Decide all values of b in the ...

College Algebra - How do you work out this problem? 3x3 + 2x2 + 3x+2 I showed ...

Algebra - A gardener has 60 feet of fencing with which to enclose a garden ...